Pengaruh Total Aset dan Ekuitas Terhadap Laba Bersih Dengan Liabilitas Sebagai Variabel Moderator pada Perusahaan Consumer Goods - Muhammad Daffa Mahendra; Ratnaningrum Ratnaningrum; Eni Endaryati; Sukemi Kamto Sudibyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to analyze the impact of total assets and equity on net income, and to test the moderating role of liabilities, in 6 public consumer goods companies listed on the Indonesia Stock Exchange during the 2020-2024 period, namely PT Campina Ice Cream Industry Tbk, PT Garudafood Putra Putri Jaya Tbk, PT Mayora Indah Tbk, PT Sariguna Primatirta Tbk, PT Ultra Jaya Milk Industry Tbk, and PT Unilever Indonesia TBK. Utilizing secondary financial statement data and moderated regression analysis with a bootstrap approach, the research found that total assets have a significant negative effect on net income, indicating a burden if not productively managed. Conversely, both equity and liabilities significantly positively affect net income, highlighting the importance of strong owner capital and strategic debt utilization. A crucial finding is that liabilities significantly positively moderate the asset-net income relationship but negatively moderate the equity-net income relationship. Overall, this study provides deeper insights into the complex dynamics of financial structure on profitability, emphasizing that strategic liability management is essential for sustainable profitability in the consumer goods sector